The Effectiveness of Touch / Don’t Touch Technique to Improving the Understanding of Sexual Abuse Prevention for Primary School Students Number 060885 in Medan City - Nasrun, Nasrun; Nasution, Nani Barorah (Indonesian Journal of Early Childhood Education Studies, 2016)
There are currently efforts to resolve cases of child sexual abuse in Indonesia by manage legally laws that provides penalties for those who engage in child sexual abuse cases. However it is still less attention in the education field, educational institutions have not been able to play an active role and become a shield to prevent child sexual abuse. In other words, it should be emphasized that prevention efforts have to be comprehensive, which is mean that not only done by one party (parents or relatives) only, but must be integrated with the government, community organizations, schools, professionals, who does have a concentration on growth and child development. In Indonesia, the Indonesian Child Protection Commission (KPAI) admits received many complaints of violence and sexual abuse of children, based on KPAI data that has been collected in the period January to March 2014. During those three months, there were 379 cases reported to the KPAI, one of which is sexual violence that afflicts kindergarten students at the Jakarta International School (JIS). Based on the data described above is carried out preventive measures to prevent the occurrence of child sexual abuse in the form of education and research. The research conducted by the author with the title " The effectiveness of touch / don’t touch technique to improving the understanding of sexual abuse prevention for primary school students in SDN No 060885 Medan ". This research is quasi-experimental research, using scale to collected the sexual abuse prevention understanding among elementry student. The research showed that the average value of the pre-test = 58.41 with a highest score of 77 and the lowest value of 49 and a standard deviation of 8.7, while for the data obtained posttest average value of post test = 75.30 with a highest score 89 and the lowest value of 61 and a standard deviation of 6.3. Based on the above data it can be concluded there was an increased understanding of the elementary school students grade 3 Elementary School SDN No. 060 885 of the hazards and sexual abuse. This means that by using the techniques touch / dont touch can enhance students' understanding and the prevention of sexual harassment preventive efforts